Precise diagnosis and treatment of non-muscle invasive bladder cancer - A clinical perspective - Yang, Yongjun; Wang, Chen; Li, Zonglin; Lu, Qiang; Li, Yuanwei (Frontiers in Oncology, 2023)
According to the guidelines, transurethral resection of bladder tumor (TURBT) followed by intravesical therapy remains the standard strategy for the management of non-muscle invasive bladder cancer (NMIBC). However, even if patients receive standard strategy, the risk of postoperative recurrence and progression is high. From the clinical perspective, the standard strategy needs to be optimized and improved. Compared to conventional TURBT, the technique of en bloc resection of bladder tumor (ERBT) removes the tumor tissue in one piece, thus following the principles of cancer surgery. Meanwhile, the integrity and spatial orientation of tumor tissue is protected during the operation, which is helpful for pathologists to make accurate histopathological analysis. Then, urologists can make a postoperative individualized treatment plan based on the patient's clinical characteristics and histopathological results. To date, there is no strong evidence that NMIBC patients treated with ERBT achieve better oncological prognosis, which indicates that ERBT alone does not yet improve patient outcomes. With the development of enhanced imaging technology and proteogenomics technology, en bloc resection combined with these technologies will make it possible to achieve precise diagnosis and treatment of bladder cancer. In this review, the authors analyze the current existing shortcomings of en bloc resection and points out its future direction, in order to promote continuous optimization of the management strategy of bladder cancer.